Determining the optimal concentration of mannose as an effective selection agent for transformed oil palm cells using the phosphomannose isomerase (pmi) gene as a positive selectable marker - Bahariah, B.; Parveez, G.K.A.; Khalid, N. (2012)
The elimination of antibiotic or herbicide resistance gene usage in genetically modified plants is being encouraged due to public concern. In response to this, alternative selection systems for the recovery of transgenic oil palm were developed using positive selectable markers. To establish a selection system that utilises the phosphomannose isomerase (pmi) gene for oil palm transformation, we first determined the optimal mannose concentration for selecting the transformed cells. Non-transformed embryogenic calli were cultured on media containing various combinations and concentrations of mannose and a usable source of carbon, i.e. sucrose, ranging in content from 0 to 30 g litre . Sucrose is often used as a carbon source in plant tissue culture media. The embryogenic calli were subcultured onto similar fresh media every four weeks, and growth was recorded monthly up to five months. From the 10 combinations of mannose and sucrose evaluated, mannose:sucrose at 30:0 g litre was shown to be the most effective for selection because at this concentration the least plant grozvth was demonstrated for non-transformed embryogenic calli. We will thereafter use this particular concentration of mannose to select for oil palm embryogenic calli transformed with the pmi gene using biolistic bombardment.